2021
DOI: 10.2147/dmso.s289446
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-Existing Diabetes Limits Survival Rate After Immune Checkpoint Inhibitor Treatment for Advanced Lung Cancer: A Retrospective Study in Japan

Abstract: Background Although immune checkpoint inhibitors (ICIs) are promising in the treatment of advanced cancer, their use is associated with immune-related adverse events (irAEs) that affect endocrine organ systems. Although development of irAEs was associated with improved cancer-specific survival, the risk of irAEs is unclear. We investigated the association of pre-ICI comorbidities—including diabetes—with irAEs, overall survival (OS), and progression-free survival (PFS) in advanced lung cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Finally, four papers were included in the Meta-analysis had a total of 3065 cancer patients of which 1509 cancer patients had diabetes mellitus and a form of cancer while 1556 patients did not have diabetes mellitus. Although the total population is large, disparity in terms of representations across the four studies is evident [11][12][13][14]. For example, study selection and contribution to this meta-analysis leads to one study contributing to the majority of participants so that 2600 cancer patients and 1395 DM patients are from a single study.…”
Section: In-depth Study Characteristics Descriptionmentioning
confidence: 99%
“…Finally, four papers were included in the Meta-analysis had a total of 3065 cancer patients of which 1509 cancer patients had diabetes mellitus and a form of cancer while 1556 patients did not have diabetes mellitus. Although the total population is large, disparity in terms of representations across the four studies is evident [11][12][13][14]. For example, study selection and contribution to this meta-analysis leads to one study contributing to the majority of participants so that 2600 cancer patients and 1395 DM patients are from a single study.…”
Section: In-depth Study Characteristics Descriptionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), including antibodies against programmed cell death-1 (PD-1) and PD-1 ligand-1 (PD-L1), induce their anti-tumor effects by improving the function of immune cells 11 . Two retrospective studies from Israel 12 and Japan 13 recently reported that diabetes was negatively correlated to overall survival in patients with non-small cell lung cancer (NSCLC) treated with ICIs. However, the mechanisms behind this impaired outcome of ICI treatments in diabetic patients remain unknown.…”
Section: Introductionmentioning
confidence: 99%